Rooting of yellow mombin cuttings (Spondias mombin L.) as a function of the application of plant regulators - Véras, Mario Leno Martins; Mendonça, Rejane Maria Nunes; Ramires, Christiane Mendes Cassimiro; Araújo, Vandeilson Lemos de; Figueredo, Lucimara Ferreira de; Alves, Lunara De Sousa; Pereira, Walter Esfrain (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
At the moment, there are no commercial  yellow mombin crops in Brazil, where fruits are harvested from extractive crops. One reason for this is the lack of a  propagation protocol for this species because the yellow mombin has a low rooting percentage for cuttings. Therefore, techniques that provide maximum rooting for cuttings are required. The objective of this study was to evaluate the effect of a matrix plant treatment with zinc on the rooting of yellow mombin cuttings treated with indolebutyric acid. In this experiment, a completely randomized design was used, with 9 treatments  arranged with pre-determined levels for the factors with  the matrix "Central Box Compound" for the zinc concentrations (0, 5.8, 20, 34.2 and 40 mg L-1) and combinations with the indolbultric acid concentrations (0, 872.35, 3000, 5127.65 and 6000 mg L-1), with 4 replicates, where each experiment unit consisted of 12 cuttings. The application of zinc in yellow mombin matrix plants had no effect on the rooting of cuttings. The 6000 mg L-1  indolebutyric acid dose provided an increase in sprouts and live cuttings with a callus; however, it did not influence the rooting.